Reducing Unnecessary Antibiotic Use for Upper Respiratory Tract Infections by Focusing On Patients - Mortazhejri, Sameh (Université d'Ottawa / University of Ottawa, 2018)
Background: Antibiotics are prescribed frequently for upper respiratory tract infections (URTIs) despite the fact that most of them do not require antibiotics. This over-prescription contributes to antibiotic resistance which is a major health problem. Physicians perceive that patients’ expectations influence their antibiotic prescribing practice. Methods: As the first phase of the thesis, we conducted a systematic review to determine the effectiveness of patient-oriented interventions to reduce unnecessary use of antibiotics for URTIs. As the second phase, we conducted a qualitative descriptive study to explore patients’ views about URTIs and identify ways they manage them by using semi-structured interviews based on Common Sense-Self-Regulation Model (CS-SRM). Results: Our systematic review included 14 studies which based on their interventions were classified into two major categories: delayed prescriptions and patient/public information and education interventions. Our meta-analysis revealed that almost all studies with delayed prescription significantly reduced use of antibiotics for URTIs. Our subgroup analysis showed that prescriptions that were given at a later time and prescriptions that were given at the index consultation had similar effects regarding antibiotic use. The small number of included studies in the patient/public information and education group did not allow us to make a definite conclusion on their effectiveness. For the qualitative study, 15 individuals were interviewed. almost all participants mentioned that they only visited their doctor if their symptoms got progressively worse and they could no longer self-manage URTI symptoms. When visiting a doctor, most participants reported that they expected to receive an examination and an explanation for their symptoms. Discussion: Patient-oriented interventions (especially delayed prescriptions) may be effective in reducing antibiotic use or prescription for URTIs in patients. Further research is needed to investigate the costs and feasibilities of implementing these interventions as part of routine clinical practice. Our participants reported good knowledge regarding the likely lack of benefit from antibiotics for URTIs. The results suggest a discrepancy between our participants’ reported reasons for visiting doctors and doctors’ perceptions about patients’ reason for their visit identified in previous studies. Focusing on interventions that facilitate the communication between patients and doctors, instead of providing more education to public may help in reducing the use of unnecessary antibiotics.
Keywords: Antibiotics; Systematic review; Common sense self regulation model; Upper respiratory tract infections; Patient-oriented